The Effect of Transformational Leadership, Servant Leadership, and Spiritual Leadership on Organizational Citizenship Behavior - Putu Gede Subhaktiyasa; Kiki Rizki Fista Andriana; Silvia Ni Nyoman Sintari; Wayan Shinta Wati; N Putri Sumaryani; Yohanes Umbu Lede (Jurnal Organisasi dan Manajemen, 2023)
Purpose - Universities are unique institutions that require different leadership styles to achieve their goals. Therefore, this research examines the effect of transformational, servant, and spiritual leadership on the Organizational Citizenship Behavior (OCB) of lecturers.  Methodology - The research adopted a quantitative approach, using a questionnaire with a Likert scale to collect data. Purposive sampling was utilized to obtain 120 participants. The SEM-PLS analysis was employed to test the research hypothesis.    Findings - The results showed that transformational leadership did not have a significant impact on OCB. Meanwhile, both servant and spiritual leadership had a positive effect on OCB. Among the three leadership styles, spiritual leadership was effective in universities, specifically in developing organizational behavior. Originality - Previous research on leadership in educational institutions only focuses on one or a few leadership styles. The current research is unique because it examines the influence of three leadership styles on OCB in universities. The variables in the proposed model are new constructs that necessitate further investigation in order to gain a better understanding of their relationship with OCB.